SWOT Analysis Strategy to Improve Topography Code Accuracy in Malignant Neoplasms Cases at Ibnu Sina Hospital Makassar - Asriyanti, Asriyanti; Meilany, Lilik; Agustina, Agustina; Putri, Rosana Dwiyanti (Journal of Aafiyah Health Research (JAHR), 2025)
ABSTRACT Background: Neoplasm insurance claims are one of the most pending cases in the claim submission process. Pending claims are caused by inaccurate neoplasm topography codes. This disrupts hospital operational costs, increases the workload of coders and affects the quality of disease statistical data. Objective: This study aims to improve the accuracy of topography codes in malignant neoplasm cases using SWOT analysis. Method: The type of research is descriptive, the sample size is 110 patient medical records, data collection is by means of observation and interviews. Results: The results of the study showed that the completeness of medical information was 32.6% and incomplete 67.4%, the accurate topography of neoplasms code was 21.8% and inaccurate 78.2%. The causes of inaccuracy were delays in the results of the Anatomical Pathology laboratory 53.2%, no writing of the site of neoplasms on the medical record sheet 33%, and coders did not pay attention to the morphology of neoplasms code 13.8%. The results of the SWOT analysis show strength and opportunity factors, namely the educational qualifications of coders according to their competencies, using the most updated ICD-10 book. Weakness and threat factors are incomplete medical information, no SOP for coding neoplasms and no periodic coding audits. Strategies to improve the accuracy of diagnostic codes by optimizing internal and external factors by conducting coding audits, preparing SOPs and improving clinical coding skills in coders.